2007
DOI: 10.1021/jo0707535
|View full text |Cite
|
Sign up to set email alerts
|

Facile, Mild, and Highly Enantioselective Alkynylzinc Addition to Aromatic Aldehydes by BINOL/N-Methylimidazole Dual Catalysis

Abstract: The dual Lewis acid/base catalytic system, generated from N-methylimidazole (NMI), (R)-1,1'-bi-2-naphthol [(R)-BINOL], and Ti(OiPr)4, effectively catalyzes the enantioselective alkynylation of aldehydes in the presence of Et2Zn in good yields and excellent enantioselectivities of up to 94% ee at room temperature. The mild reaction conditions make it possible to use functional alkynes in this asymmetric addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 38 publications
0
30
0
1
Order By: Relevance
“…All compounds were prepared starting from 5.0 mmol of the appropriate alkyne. [34] 3-Propargyl-2-acylindoles 5a-g are new compounds and were prepared as reported in ref. [25] starting from 2 mmol of 8a,b.…”
Section: Methodsmentioning
confidence: 99%
“…All compounds were prepared starting from 5.0 mmol of the appropriate alkyne. [34] 3-Propargyl-2-acylindoles 5a-g are new compounds and were prepared as reported in ref. [25] starting from 2 mmol of 8a,b.…”
Section: Methodsmentioning
confidence: 99%
“…However, to our knowledge, the enantioselective trimethylsilylacetylene addition of hetroaromatic, a,b-unsaturated aldehydes has attracted less attention yet. 53 In addition, only the asymmetric addition of ethynylcyclohexene to benzaldehyde has been reported, 31,34,54 and the maximum ee value is just 90%, whereas the catalytic asymmetric addition of ethynylcyclohexene to other aromatic and aliphatic aldehydes has not been yet reported. From a practical standpoint, it is still necessary to develop efficient and practical catalysts for this asymmetric transformation.…”
Section: Introductionmentioning
confidence: 99%
“…We initiated the reaction of methyl propiolate with isovaleraldehyde in the presence of 0.25 equiv chiral ligand 4a, diethylzinc, and titanium tetraisopropoxide in toluene, the expected propargylic alcohol was obtained in 75% ee (Table 1, entry 1). Some reports have shown that the Lewis bases can enhance the reaction of alkynoates with aldehydes 4c, 9,13 and that the Lewis base played an important role in this reaction. In comparison with the Lewis bases HMPA and 1,2-dimethoxyethane (DME), tertiary amine N-methylimidozole (NMI), triethylamine (TEA) and N,N,N,N-tetramethylethane-1,2-diamine (TMEDA) are stronger bases.…”
Section: Resultsmentioning
confidence: 99%